S-wave velocity characteristics and mineralization of the southern tibet detachment system-yalaxiangbo dome - Wang, Guangwen; Lu, Zhanwu; Li, Wenhui; Wang, Haiyan; Xue, Shuai; Cheng, Yongzhi; Chen, Si; Wang, Hao; Wu, Guowei; Cai, Wei (Frontiers in Earth Science, 2023)
A series of extensional structures, including the southern Tibet detachment system (STDS), the north-south trending rifts (NSTR), and the northern Himalayan gneiss dome (NHGD), developed from the collision and compression between the Indian and Eurasian plates. These tectonic movements were accompanied by magmatism and polymetallic mineralization. Cuona Rift (CR) is located on the STDS next to the Yalaxiangbo Dome (YD) and passes through the Zhegucuo-longzi fault (ZLF), the Lhozhag fault (LZF), the Rongbu-Gudui fault (RGF), the Cuonadong dome (CD), and the YD. The study area contains numerous metal deposits, such as rare metal ore, lead zinc ore, gold deposits, and two geothermal fields, i.e., the Cuona geothermal field (CGF) and the Gudui geothermal field (GGF). Current research on the geological structures from the STDS to the YD is mainly based on magnetotelluric and natural seismic imaging. These surveys have a low resolution, making it impossible to image the shallow crust in detail. This study obtained about a 112 km S-wave velocity profile from the STDS to the YD using the multichannel surface wave imaging method. The profile results indicated that the average thickness of the sedimentary layer from the STDS to the YD is 400–500 m, while it is more than 800 m at certain fault zones. The CD is connected to the high-velocity body below the Zhaxikang ore concentration area (ZOCA) and may have the same provenance. The thermal conductivity reveals that the CGF, the GGF, and the ZOCA have high values and a more intense thermal radiation capacity. This drives the migration and circulation of the thermal fluids in the CGF and the GGF, causing them to continuously transmit heat to the shallow surface along the fault system. The migration of the thermal fluids extracts useful elements from the geological bodies through which it flows. When these elements mix with the atmospheric infiltration water, it precipitates to form the Zhaxikang hydrothermal superimposed transformation type lead-zinc polymetallic deposit.